Analisis Kinerja Keuangan dan Strategi Manajemen PT Bukalapak.com Tbk Pra & Pasca Initial Public Offering (IPO) - Frymaruwah, Edwin; Andrian, Pieter; Tecoalu, Melitina (Owner : Riset dan Jurnal Akuntansi, 2024)
The research aims to analyze differences in company financial performance before and after the Initial Public Offering. The research period is three years before and two years after the IPO. The object of this research is PT Bukalapak.com Tbk which is conducting an IPO in 2021. The analytical method used is the Analysis of Financial Liquidity Ratios, Activity Ratios, Profitability Ratios, and Solvency Ratios and in-depth interviews with the person in charge (key person) of the company to confirm and strengthen the analysis results. The research results show that there are significant differences in the company's financial performance, namely liquidity, activity, and solvency before and after the IPO, while the company's profitability experienced a decline in performance after the IPO in the first year and improved in the second year after the IPO until it was able to record its first positive performance in the second year after the IPO.